2020
DOI: 10.1016/j.seizure.2019.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Change in the strategy for prophylactic diazepam use for febrile seizures and the impact on seizure recurrence within 24 h

Abstract: To investigate the association between reduced prophylactic diazepam usage and short-term recurrence of febrile seizures (FSs) after the FS practice guideline was updated in Japan. Method: In this single-center, retrospective study, children (6-60 months of age) with FS who were transported to our center by ambulance from January 2011 through December 2018 were included. Rectal administration of diazepam (0.3-0.5 mg/kg) after the first seizure and seizure recurrence within 24 h were compared between 2011-2015 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The prophylactic use of diazepam has been controversial. In a retrospective study in Japan comparing rectal administration and seizure recurrence within 24 h of the first seizure, in 2011–2015 (when prophylactic diazepam use was recommended before guideline revision) and in 2016–2018 (when routine diazepam use was not recommended after guideline revision), results showed an association between increased FS recurrence within 24 h and decreased prophylactic diazepam use ( Inoue et al, 2020 ). However, a recent meta-analysis showed that for children at increased risk of frequent or complex seizures, although intermittent diazepam and continuous phenobarbital may reduce the recurrence rate, the adverse effects are up to 30%; therefore, intermittent and continuous treatment with antiepileptic drugs is not recommended and families and parents should receive sufficient information about the disease ( Offringa et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prophylactic use of diazepam has been controversial. In a retrospective study in Japan comparing rectal administration and seizure recurrence within 24 h of the first seizure, in 2011–2015 (when prophylactic diazepam use was recommended before guideline revision) and in 2016–2018 (when routine diazepam use was not recommended after guideline revision), results showed an association between increased FS recurrence within 24 h and decreased prophylactic diazepam use ( Inoue et al, 2020 ). However, a recent meta-analysis showed that for children at increased risk of frequent or complex seizures, although intermittent diazepam and continuous phenobarbital may reduce the recurrence rate, the adverse effects are up to 30%; therefore, intermittent and continuous treatment with antiepileptic drugs is not recommended and families and parents should receive sufficient information about the disease ( Offringa et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that prophylactic diazepam had the potential to minimize the risk of FS recurrence within 24 hours and given only while the fever was present. [29][30][31][32][33] Additionally, consensus on the management of FS by Indonesia's Pediatricians Association stated that the use of oral diazepam or rectal diazepam in every 8 hours at fever of >38.5°C can minimize the risk of recurrent FS in 30 to 60% cases. 34 Most of the patients in this study reported having simple FS, similar to the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study done in Japan from 2011 to 2018, there was an increase in the recurrence of FS with a decrease in the dose of diazepam compared to the year. This concludes the potential use of rectal administration of diazepam as a prophylactic agent [21]. Another comparative double-blind trial was done to analyze the difference between the continuous use of sodium valproate and phenobarbitone in the prevention of simple FS.…”
Section: Prevention and Prognosismentioning
confidence: 93%
“…A single-center retrospective study conducted in Japan in 2020, among six- to 60-month-old children, suggested that when the use of rectal diazepam was decreased, there was a significant rise in hospital revisits for the cases of recurrences of FS [ 21 ]. In another RCT study done in the Netherlands on the prophylactic use of ibuprofen syrup for a reduction in the recurrent attack of FS, no significant reduction in the rates of recurrence of FS was noticed by giving ibuprofen syrup prophylactically with the increasing body temperature in children [ 22 ].…”
Section: Reviewmentioning
confidence: 99%